Non-performing loans and the lending channel of shock transmission across countries - Hoang Tuan Dao; Taesu Kang (Cogent Business & Management, 2022)
Recent international macroeconomics literature on global imbalances explains the U.S. persistent current account deficit and emerging countries' surplus. Little research has been done at the banking-sector level, where U.S. banks are lenders to banks in emerging countries. We build a two-country framework where banks are explicitly modeled to investigate how lending in the banking sector can affect the international macroeconomy during the financial crisis of 2007-2008. In the steady state, banks in the developing country borrow from the U.S. banks. When the borrowers in the U.S. pay back less than contractually agreed and damage the balance sheet of the U.S. banks, with the presence of bank capital requirement constraint, U.S. banks raise lending rates and decrease the loans made to U.S. borrowers as well as banks in the developing country. The results are a sharp increase in the lending spread, a reduction in output and a depreciation in the real exchange rate of the developing country. This is the experience of many emerging Asian markets following the U.S. financial crisis starting in late 2007. Another feature of our model captures an empirical fact, documented by Devereux and Yetman, that across different economies, countries with lower financial ratings can suffer more when the lending country deleverages.
Keywords: 650; financial crisis; bank deleverage; emerging Asian markets; International finance; real exchange rate